Analisis Jurnal Terhadap Faktor Genetik yang Mempengaruhi Pertumbuhan dan Perkembangan Pada Manusia - Miftahul Khairani; Adyla Syukrhaini Marwi; Isnaini Rahmah Lubis; Putri Rizq Achyari; Qoyum Amalia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Human growth and development is a complex process, influenced by environmental and genetic factors. This article aims to conduct an analysis of journals that examine genetic factors that influence growth and development in humans. Through searches of various scientific journal databases, this article examines the research methods used, main findings, and implications of research results relevant to genetic factors that play a role in human growth and development. This analysis highlights studies that examine genetic polymorphisms, gene expression, gene mutations, and other genetic factors that play a role in the regulation of physical growth, cognition, and other aspects of human development. The implications of these findings are the main focus of this article, including how this knowledge can be applied in the clinical field, including further understanding of growth and development disorders caused by genetic factors. The results of this journal analysis provide a deeper understanding of the complexity of interactions between genetic factors and growth and development in humans, as well as their relevance in the clinical field and advanced research. The practical implications can also potentially impact the diagnosis, management, and therapy planning for individuals with growth and developmental disorders that are influenced by genetic factors.